Revitalisasi Perpustakaan dalam Meningkatkan Minat Baca Warga Binaan di Lapas Narkotika Kelas IIB Banyuasin - Annisa Nur Aziza; Umar Anwar (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The revitalization of the library at Lapas Narkotika Kelas IIB Banyuasin is part of an effort to enhance inmates’ reading interest as a form of social and educational rehabilitation within the correctional institution. This initiative aims to optimize the library’s function as a learning and empowerment facility for inmates. The research methods include observation, interviews, social assessments, and interventions such as providing reading materials, reorganizing the library, and promoting literacy through shared reading activities. The results indicate an increase in inmate participation in utilizing the library after revitalization. Additionally, there was a positive impact on their motivation to improve reading skills and comprehension, which supports their social reintegration process. Recommendations from this study include diversifying the book collection, integrating technology into the library system, and enhancing collaboration with external communities to sustain literacy programs within the correctional facility.